Regulation of aquaporin-2 using traditional Chinese medicine in water balance disorders: a literature review - Chang, Yifan; Liu, Lu; Xu, Xiaodong; Zhang, Shiqiang (Frontiers in Cardiovascular Medicine, 2025)
Aquaporin-2 (AQP2) is a critical protein involved in water metabolism. It is primarily located in the renal collecting duct cells’ apical plasma membranes and intracellular vesicles and regulates the movement of water into and out of cells. It plays a pivotal role in maintaining fluid balance, and its dysregulation is associated with conditions such as hypertension and heart failure, which contribute to cardiovascular disease progression. AQP2 has garnered significant attention as an emerging therapeutic target. Traditional Chinese medicine (TCM) has demonstrated efficacy in treating water balance disorders, although its underlying mechanisms remain elusive. The discovery of AQP2 and its association with water metabolism provides an opportunity for TCM to explore these mechanisms more intuitively. This review integrates TCM formulas, single herbs, and active constituents, linking them to AQP2 regulation in the kidneys, heart, liver, inner ear, and uterus with an emphasis on the AVP–V2R–AQP2 axis, while distinguishing between short- and long-term regulation and highlighting cardiovascular applications. This review synthesizes the current evidence from experimental and limited clinical studies, highlights the regulatory effects of TCM on AQP2 in various organ systems, and identifies key research gaps to guide future translational and clinical investigations.